PERCEPTION OF PEOPLE ON AADHAAR (LINKAGE, USAGE & VOTING) A CASE STUDY (2014-16) WITH REFERENCE TO CHITTOOR DISTRICT AP, INDIA - Raaju (International Journal of Research -GRANTHAALAYAH, 2017)
This article is a survey done to know how the people linked their aadhaar number to the voter id, gas cylinder, fee reimbursement, Bank account, House & Water tax, Birth Certificate, Admission in a School, RTO license, Raitu Runa Mafi, Employer data, Income/Caste/ Nativity. This article also collected the information on how is the usage of aadhaar as a proof of identity and the people voting on continue the aadhaar and linking of aadhaar.